2018
DOI: 10.1186/s13028-018-0366-8
|View full text |Cite
|
Sign up to set email alerts
|

Orf virus infection in Alaskan mountain goats, Dall’s sheep, muskoxen, caribou and Sitka black-tailed deer

Abstract: BackgroundThe zoonotic Orf virus (ORFV; genus Parapoxvirus, Poxviridae family) occurs worldwide and is transmitted between sheep and goats, wildlife and man. Archived tissue samples from 16 Alaskan wildlife cases, representing mountain goat (Oreamnos americanus, n = 8), Dall’s sheep (Ovis dalli dalli, n = 3), muskox (Ovibos moschatus, n = 3), Sitka black-tailed deer (Odocoileus hemionus sitkensis, n = 1) and caribou (Rangifer tarandus granti, n = 1), were analyzed.ResultsClinical signs and pathology were most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 28 publications
(35 reference statements)
1
23
0
Order By: Relevance
“…The mechanism of inter species transmission of CePV1v should be studied further in the light of the fact that other Delta papillomaviruses have already shown to be transmissible even to phylogenetically distant animal species thus host tropism of papillomaviruses is not as species-specific as previously thought (22). The genetic characterization of the PPV infecting chamois and ibex suggested that OV has an ecological niche in chamois and ibex as reported for other wildlife species worldwide (39). Nevertheless, phylogenetic analysis of the conserved B2L gene showed that all strains of chamois and ibex grouped with other isolates from sheep and goats instead of clustering by animal species confirming the high genomic variability of the OV species and the susceptibility of wildlife species.…”
Section: Discussionmentioning
confidence: 91%
“…The mechanism of inter species transmission of CePV1v should be studied further in the light of the fact that other Delta papillomaviruses have already shown to be transmissible even to phylogenetically distant animal species thus host tropism of papillomaviruses is not as species-specific as previously thought (22). The genetic characterization of the PPV infecting chamois and ibex suggested that OV has an ecological niche in chamois and ibex as reported for other wildlife species worldwide (39). Nevertheless, phylogenetic analysis of the conserved B2L gene showed that all strains of chamois and ibex grouped with other isolates from sheep and goats instead of clustering by animal species confirming the high genomic variability of the OV species and the susceptibility of wildlife species.…”
Section: Discussionmentioning
confidence: 91%
“…The diagnosis is often based on clinical signs and characteristic tissue alterations in affected animals. The clinical features found in infected animals vary from multiple lesions around the lips, muzzle, nostrils, teats and oral mucosa, with occasional spread to the buccal cavity, oesophagus, stomach, intestine or the respiratory tract (Nandi et al, 2011;Maganga et al, 2016;Tryland et al, 2018). Despite very developed characteristic clinical symptoms, and in order to exclude other contagious diseases, two suspect ORF infections that were reported in 2016 were confirmed in the laboratory by the virus isolation, PCR, and genome sequencing.…”
Section: Discussionmentioning
confidence: 97%
“…Sheep and goats are most susceptible for ORFV infection, but the other ruminants such as musk ox, camels and reindeer can be infected (Mombeni et al, 2013;Tryland et al, 2018). ORFV has also zoonotic potential affecting people who work with animals (Zhang et al, 2014b;Bergqvist et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Further viruses include papillomaviruses, parvovirus, and polyomavirus, as well as importantly also Coronaviridae [ 131 ]. Experimental viral infections in reindeer include herpesvirus 2 and parapoxvirus, both of which have though also been detected in Norwegian reindeer [ 129 ], including semi-domesticated reindeer [ 132 ] as well as in Alaskan caribou and other wildlife, and are known to be transmitted between wildlife, sheep, goats and human [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The IUCN Red List of Threatened Species (2016) has classified reindeer as a vulnerable species due to a decline of individuals, possibly attributed to habitat shift and/or their susceptibility to chronic wasting disease (CWD), a fatal neurodegenerative disorder [ 3 , 4 ]. Importantly also, R. tarandus may play roles in various zoonotic diseases, including parasitic, bacterial and viral ones [ 5 , 6 , 7 , 8 ], and deer have furthermore been recently identified to be new reservoir hosts for SARS-CoV-2 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%